Thyroid Diseases in Childhood Recent Advances from Basic Science to Clinical Practice - Bona, Gianni; De Luca, Filippo; Monzani, Alice; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book covers the entire spectrum of thyroid diseases in childhood, focusing on the recent advances that have been achieved, from progress in basic science research through to novel or improved approaches to diagnosis and treatment. Introductory chapters discuss thyroid embryogenesis and the role of thyroid hormones in fetal development. The two contrasting forms of thyroid dysfunction, hypo- and hyperthyroidism, are then considered in depth, with particular attention to the molecular causes of congenital hypothyroidism. Among the other topics addressed are autoimmune thyroiditis, thyroid nodules, and pediatric neoplasms. The book concludes with an overview of promising therapeutic approaches, such as stem cell therapy. Each topic is treated by an eminent expert in the field, ensuring consistently high quality. Thyroid Diseases in Childhood will be an important source of information for endocrinologists, pediatricians, oncologists, and gynecologists, as well as other professionals interested in this topic.
Thyroid embryogenesis -- Thyroid hormones in fetal development -- Etiology of congenital hypothyroidism -- Neonatal screening for congenital hypothyroidism: what it has taught us about thyroid and brain -- Laboratory aspects in neonatal screening of congenital hypothyroidism -- Epidemiology of congenital hypothyroidism -- Congenital hypothyroidism due to PAX8 mutations -- Transient neonatal hypothyroidism -- Central Hypothyroidism -- Syndromes of resistance to thyroid hormone action -- Management of congenital hypothyroidism -- Neurodevelopmental outcomes in children with congenital hypothyroidism -- Iodine deficiency from pregnancy to childhood -- Thyroid enlargement from newborn to adolescent -- Thyroid nodules and carcinoma -- Autoimmune thyroiditis -- Subclinical hypothyroidism -- Hyperthyroidism -- Generation of functional thyroid from embryonic stem cells.
Keywords: Endocrinology .; Pediatrics; Oncology .; Endocrinology; Pediatrics; Oncology